Associations between personality traits and pain experiences in trigeminal neuralgia - Jeong-A Lee; Yoon Kyung Han; Won Je Jung; Byung H. Lee; Seunghoon Lee (The Journal of Headache and Pain)
Abstract Background Pain is influenced by many factors such as personality traits and nociceptive stimuli. This study identified personality traits in patients with trigeminal neuralgia (TN) and investigated the relationships between personality traits and pain perception, pain acceptance, anxiety, and depression. Methods From March to June 2024, the personality traits of 50 patients with TN and 50 healthy controls (HC) were measured using the 50-item International Personality Item Pool representation of Goldberg markers for the Big-Five factor structure. Patients’ pain perception, pain acceptance, anxiety, and depression were measured. Results The mean neuroticism scores and median anxiety and depression scores of patients with TN were higher than those of HC (p = 0.006, p < 0.001, and p = 0.010). There were no significant differences in pain perception and pain acceptance according to the personality traits. The higher the neuroticism score, the higher the anxiety and depression scores (ρ = 0.437, p = 0.002 and ρ = 0.344, p = 0.014). The higher the anxiety score, the higher the pain catastrophizing score, and the lower the pain acceptance score (ρ = 0.488, p < 0.001 and ρ = -0.365, p = 0.009). Higher depression score was associated with a pain frequency of 11 or more times per 24 h (odds ratio = 1.243, p = 0.015). The higher the depression score, the lower was the pain acceptance score (ρ = -0.324, p = 0.022). Conclusions In patients with TN, neuroticism was not associated with pain. However, higher levels of neuroticism were associated with higher levels of anxiety and depression, and higher levels of anxiety and depression were associated with higher pain catastrophizing or pain frequency, and lower pain acceptance. These results can be used to establish individualized treatments for patients with TN, that focus on their emotional states according to personality traits, such as adapting psychological therapies differently for individuals with high neuroticism.